2022
DOI: 10.3324/haematol.2022.281640
|View full text |Cite
|
Sign up to set email alerts
|

International multicenter retrospective analysis of thiotepa-based autologous stem cell transplantation for secondary central nervous system lymphoma

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The largest series of 134 SCNSL patients undergoing thiotepa-based ASCT reported 3-year overall and progression-free survival rates of 71.6% (95% CI: 61.9%-not reached) and 61.1% (95% CI: 52.2-68.9%), respectively. 56 One-hundred-day non-relapse mortality was 3% and the cumulative incidence at 1 and 3 years was 8.4% (95% CI: 4.7-14.6). The risk factors determining progression after SCNSL were similar to those prior to ASCT.…”
Section: Treatment Approach For Secondary Central Nervous System Lymp...mentioning
confidence: 91%
See 2 more Smart Citations
“…The largest series of 134 SCNSL patients undergoing thiotepa-based ASCT reported 3-year overall and progression-free survival rates of 71.6% (95% CI: 61.9%-not reached) and 61.1% (95% CI: 52.2-68.9%), respectively. 56 One-hundred-day non-relapse mortality was 3% and the cumulative incidence at 1 and 3 years was 8.4% (95% CI: 4.7-14.6). The risk factors determining progression after SCNSL were similar to those prior to ASCT.…”
Section: Treatment Approach For Secondary Central Nervous System Lymp...mentioning
confidence: 91%
“… 55 Most patients relapse early and are therefore resistant to primary therapy in both compartments. The minority are chemo-responsive, but those who undergo ASCT have better outcomes (3-year progression-free survival 40%) 56 so this should be the treatment goal. Systemic treatment options include RICE and RDHAP (rituximab, cytarabine, cisplatin and dexamethasone) ( Figure 2 ).…”
Section: Treatment Approach For Secondary Central Nervous System Lymp...mentioning
confidence: 99%
See 1 more Smart Citation
“…The best survival outcomes are for patients with SCNSL who undergo ASCT consolidation 19 . A retrospective study of 134 patients undergoing ASCT (38% TN, 62% R/R) reported a 2‐year PFS of 61%, far exceeding expected outcomes for all patients with SCNSL 32 ; ASCT consolidation is now widely used and routinely incorporated in prospective SCNSL trials (Table 1).…”
Section: Consolidation Autologous Stem Cell Transplantation In Scnslmentioning
confidence: 99%
“…The MARIETTA trial reported a 14% 2‐year PFS for 28 patients with RC‐SCNSL, consistent with other studies of this population. Whilst previous studies report significantly improved outcomes (46% 2‐year PFS) for responding patients receiving consolidation TT‐based ASCT, 32 the majority of patients in MARIETTA did not proceed to ASCT despite an overall response rate (ORR) of 46% 19 . Fitness for intensive treatment, anticipated benefit and patient wishes must be taken into consideration; palliative approaches may be more appropriate for many patients (Figure 2).…”
Section: Treatment Approaches For Scnslmentioning
confidence: 99%